PELATIHAN PEMANFAATAN ARTIFICIAL INTELLIGENCE (AI) DALAM MENINGKATKAN KETERAMPILAN MENGAJAR GURU SMA NEGERI 1 SIDRAP - Raden Wirawan; Agunawan; Muhammad Yassir; Muhammad Rijal; Nurani; Eka Wijaya Paula; Aulyah Zakilah Ifani; Nurul Istiqamah; Muthi Syahidah Arifuddin; Fyan Wijaya Komputra Ahmadi; Masyita Risna (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2025)
This service activity aims to provide information about the development of AI in the world of education and the use of AI information technology to support learning activities. The target of the activity is teachers at SMA Negeri 1 Sidrap. The activity was carried out for 1 day with stages of preparation, problem solving, implementation and monitoring and evaluation. The focus of implementing this activity is the introduction of AI tools that are easy to use and focused on how to utilize information technology to improve teacher performance.  The results of the training on the Use of Artificial Intelligence (AI) in education at SMA Negeri 1 Sidrap went smoothly and will help create a learning environment that is more effective, efficient and responsive to the needs of students and teachers.